The Correlation Between Reading Ability And Self-Regulated Reading in Digital Text - Laeli, Anita Fatimatul (Universitas Muhammadiyah Jember, 2024)
The research aims to investigate two main questions: first, whether there exists a correlation between the extensive use of self-regulated reading and the reading proficiency of aspiring English teachers, particularly in digital text comprehension; second, which specific components of self-regulated reading are predominantly employed by these preservice English teachers. The research adopts a quantitative approach, employing a correlational study design, with 37 sixth-semester students in English language education as participants. Data collection involves using a questionnaire and gathering participants' reading scores. The analysis is conducted using correlation and descriptive statistics in Microsoft Excel. Results indicate a weak negative correlation of -0.02116, suggesting a discrepancy between student's reading abilities and their reported self-regulated reading habits in online texts. In conclusion, there is a minimal negative association between students' reading proficiency and online reading proficiency. Future research should delve deeper into this relationship, incorporating specific assessments of online reading proficiency. Furthermore, researchers can also consider additional variables, such as students' level of technological skills or preferences for digital learning, to enrich the understanding of the dynamics of the interaction between reading ability and self-regulated reading in the context of online text.